Exploring Repurchase Intention and Key Factors in Dental Care Decisions: Evidence from Dental Clinics in Bandung City, Indonesia - Suprayogi, Yogi; Mangruwa, Rajiv Dharma; Suryono, Herdiansyah Gustira Pramudia; Ramadhian, Mochamad Arief Rahman (JURNAL ILMIAH EDUNOMIKA, 2025)
This study seeks to identify the factors that influence patient repurchase intentions in dental clinics in Bandung, Indonesia, as well as how these factors interact to determine patients' decisions to return to the clinic. Based on a survey of 177 respondents, this research identifies five main factors influencing repurchase intention: quality of medical service, physical and emotional comfort, trust in the professionalism of doctors, prices, and social influences from family and friends. The analysis shows that both social influence and service quality significantly influence the repurchase intention, which social influence has the most significant influence on repurchase decisions. These findings provide important insights for dental clinics in designing marketing and service strategies that focus on improving the overall quality of the social influence and service quality, which can increase repurchase intentions. This research also promotes the development of the knowledge on health service marketing, in the context of the dental care industry in Indonesia. Keywords:​ repurchase intention, service quality, social influence.